MUSA YAKUB (HAYATI - ŞİİRLERİ ) - KILINÇ, AHMET (Fırat Üniveristesi, 2015)
Musa Yakub, kendine özgü üslubuyla insanı merkeze alarak dönemine ışık tutan Çağdaş Azerbaycan şairlerinden biridir. Şair, sadece bireyi anlatmakla yetinmez. Aynı zamanda bireyin yaşadığı toplumu da tahlil ederek çok yönlü insan ve toplum profili çizer. Yaşadığı sosyal ortamdan kopmadan eserlerini topluma mal eden şair, halk ozanı olarak millî bir kimlik kazanır. Bu açıdan yaşadığı bölgenin ve zamanın ötesine uzanarak sınırları aşan Musa Yakub, evrensele ulaşmanın çabası içerisindedir. Çalışma; şairin hayatı, edebî şahsiyeti ve şiirlerindeki izleklerin bilimsel yorumlarının yanı sıra şairi tanıtıcı bilgi ve belgeler içerir. Anahtar Kelimeler: Musa Yakub, şair, şiir, izlek, yapı, birey, toplum.

Musa Yakub is one of the contemporary Azerbaijani poets who shed light on his period by his unique style, taking the human beings in the centre. The poet does not only describe the individual. He also draws a versatile profile of man and the society by analyzing the community in which the individual lives. The poet, who appropriates his works to the society without having disconnected from the social environment where he lives, he gains a national identity as a minstrel as well. In this respect, Musa Yakub, who is extending beyond the region and time and goes over the limits, makes efforts to achieve the universality. The Study, besides the poet's life, his literary identity and the scientific interpretation of the paths of the poets, contains the introductory information and documents about the poet as well. Keywords: Musa Yakub, poet, poetry, theme, structure, individual, society.
Musa Yakub (Life – poems)
Keywords: Türk Dili ve Edebiyatı